Prediksi Attitude, Subjective Norms, Perceived Behavioral Control, dan Persepsi Resiko terhadap Intensi untuk Berinvestasi di Mata Uang Kripto - Prawiro, Ferdinand; Vincent, Nicholas (Atma Jaya Catholic University of Indonesia, 2025)
Crypto currency is a digital-based asset that functions as an investment instrument, a means of depositing money, and a medium for transfers through virtual networks. The rapid growth in the value of crypto currencies has increased interest among potential investors and attracted media attention to crypto currency investments. However, there is limited information whether the public is fully aware of the risks or dangers associated with investing in crypto currencies. This study aims to identify predictors of individuals’ intentions to invest in crypto currencies. The research utilized a quantitative approach with a correlational design and was analysed using multiple regression techniques. The characteristics of the participants were as follows: residents of the Greater Jakarta area (Jabodetabek), aged 18 to 21 years, having heard of crypto currency investment methods, never having invested in crypto currencies, and not currently bearing the daily expenses of others. Participants were selected using a convenience sampling technique, resulting in a total of 159 respondents. The findings show that perception of risk and attitude do not significantly predict investment intentions. However, subjective norms and perceived behavioural control significantly predict individuals’ intentions to invest in crypto currencies. Among these, perceived behavioural control was found to be the strongest predictor of individuals’ intentions to invest in crypto currencies.